PENGARUH JUMLAH TITIK PARKIR, JUMLAH PETUGAS PARKIR DAN JUMLAH KENDARAAN TERHADAP PENERIMAAN RETRIBUSI PARKIR DI KOTA PALU - Faisal, Moh. (Katalogis, 2017)
The aims of the study are : 1) to determine the effect of the number of parking spots towards parking fees amount; 2) to determine the effect of the number of parking staff toward parking fees amount; 3) to determine the effect of the number of vehicles towards parking fees amount; 4) to determine the effect of the number of parking spots, parking staff, and vehicles on the amount parking fees in Palu City. There are 4 districts involved in the study that are selected through purposive sampling. Research method is descriptive qualitative and the data is analyzed with multiple linear regressions analysis. The result concludes that : 1) the number of parking spots partially has significant effect on the amount of parking fees received with coefficient determinant of 0,727 and significant level of 0,027; 2) the number of parking staff has insignificant influence on the amount of parking fees received with coefficient determinant of 0,142 and significant level of 0,626; 3) the amount of vehicles partially has significant influence on the amount of parking fees received with coefficient determinant of 0,352 and significant level of 0,023; 4) the number of parking spots, parking staff, and vehicles simultaneously have significant influence on the amount parking fees received with coefficient determinant of 0,727 and significant level of 0,027.